Floristic study of the Asteraceae family in the “Casa de Pedra” site and adjacent areas, Bagé, Rio Grande do Sul, Brazil - Ritter, Mara Rejane (2005)
The Asteraceae family is cosmopolitan, but it is better represented in temperate and subtropical regions around the world. There is a large number of species in Rio Grande do Sul, mainly in grassland regions. The “Casa de Pedra” region, located in the Bagé municipality, is characterized for its rocky formations which stand out on its wavy landscape. The floristic composition of this site was surveyed by collecting representatives of this family that were blooming in all environments during different times of the year. The total numbers recorded were 87 species of 47 genera distributed within 12 tribes. Most of them are herbs (47) and sub-shrubs (28). The greater number of species were found on the sides road, on fields with rocky outcrops, and ongrazed fields, with 47, 30, and 25 species respectively. A greater number of blooming specimens was found during springtime and summertime, Heterothalamus allienus Kuntze and Baccharis and Senecio species stood out. Two locally situated species, Mikania capricorni B.L. Rob. and M. variifolia Hieron., are cited as threatened species on the endangered species list of plants in Rio Grande do Sul state. The large number of Asteraceae found confirms the importance of this family in the state.